2011
DOI: 10.1038/modpathol.2011.90
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HuR, COX-2, and survivin in lung cancers; cytoplasmic HuR stabilizes cyclooxygenase-2 in squamous cell carcinomas

Abstract: Hu antigen R (HuR) is a member of the human family of embryonic-lethal, abnormal vision-like proteins, which serves as an mRNA-binding protein. In the cytoplasm, HuR can stabilize the mRNA of cyclooxygenase-2 (COX-2), an enzyme that catalyses the synthesis of prostaglandins and is associated with promotion of carcinogenesis and tumor cell resistance to apoptosis. Intracellular (cytoplasmic and nuclear) localization of survivin has a prognostic significance as an apoptosis inhibitor and a regulator of cell divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 39 publications
2
22
1
Order By: Relevance
“…They found that in normal intestinal epithelium, miR-16 bound to COX-2 mRNA and inhibited its expression via promoting cox-2 mRNA decay, and that when HuR was overexpressed, miR16 could no longer bound to the cox-2 transcript, leading to COX-2 overexpression [40]. In lung cancer, similar interplays between HuR and COX-2 have been reported as well [23,38]. Other putative miR16 targets include BCL2 and NF-kappaB1/MMP-9 signaling pathway [41].…”
Section: Mirnas Mir16 and Mir519 Are Down Regulated In Tumor Tissuementioning
confidence: 82%
See 1 more Smart Citation
“…They found that in normal intestinal epithelium, miR-16 bound to COX-2 mRNA and inhibited its expression via promoting cox-2 mRNA decay, and that when HuR was overexpressed, miR16 could no longer bound to the cox-2 transcript, leading to COX-2 overexpression [40]. In lung cancer, similar interplays between HuR and COX-2 have been reported as well [23,38]. Other putative miR16 targets include BCL2 and NF-kappaB1/MMP-9 signaling pathway [41].…”
Section: Mirnas Mir16 and Mir519 Are Down Regulated In Tumor Tissuementioning
confidence: 82%
“…Recently, in a series of 81 surgically resected NSCLC, Giaginis et al reported that total HuR overexpression was correlated with poor clinical outcome [23]. On the contrary, Kim et al did not find any significant correlation between HuR and prognosis, despite the inclusion of 244 cases of NSCLC [38]. In our study, we found a significant cytoplasmic overexpression of HuR in tumor tissues vs. the adjacent normal tissue, but we found no significant correlation between the cytoplasmic staining of HuR and survival.…”
Section: Hur Is Overexpressed In Lung Cancermentioning
confidence: 96%
“…However, HuR exerts its effects in two distinctive ways. First, HuR can act as a positive regulator of gene expression by increasing the stability of target mRNAs, such as cox-2, cyclin D1, p21 and so on [13,41,42]. However, HuR has also been found to decrease the translation efficiency of some mRNAs, such as TNFα, c-myc, and p27 [43,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the stabilizing protein ELAVL1 is strongly associated with proliferation: in cancer cell models, mice and in humans [6166]. In fact, the link between ELAVL1 and cancer was initially discovered through observations of increased TNFα, VEGF, TGFβ, COX2, and CXCL8 mRNA expression in colon or brain cancer cells [67–69].…”
Section: Are-bps In Cancermentioning
confidence: 99%